2018 Korean liver cancer association-national cancer center korea practice guidelines for the management of hepatocellular carcinoma - Korean Liver Cancer Association, KLCA; National Cancer Center, NCC (Gut and liver, 2019)
Hepatocellular carcinoma (HCC) is the fifth most common cancer globally and the fourth most common cancer in men in Korea, where the prevalence of chronic hepatitis B infection is high in middle-aged and elderly patients. These practice guidelines will provide useful and constructive advice for the clinical management of patients with HCC. A total of 44 experts in hepatology, oncology, surgery, radiology and radiation oncology in the Korean Liver Cancer Association-National Cancer Center Korea Practice Guideline Revision Committee revised the 2014 Korean guidelines and developed new recommendations that integrate the most up-to-date research findings and expert opinions.